Fostering Assessment Literacy: Enhancing Teaching and Learning in Modern Education Systems - Oyeronke Christiana Paramole; Moses Adeleke Adeoye; Yejide Adepeju Ibkunle (Universitas Sebelas Maret, 2025)
Assessment literacy is a critical yet underdeveloped component of teacher competency in many educational systems. In Kwara State, Nigeria, educators face persistent challenges in designing and implementing assessments that effectively support student learning. This study investigates the assessment literacy of public secondary school educators, focusing on their understanding of key assessment principles, the strategies they employ, and the relationship between their assessment practices and student academic achievement. A mixed-methods approach was adopted, combining quantitative surveys with semi-structured interviews. Data were collected from 232 educators, with 205 valid responses (88.3% response rate), and complemented by NECO examination performance data. Descriptive statistics and regression analysis were used to evaluate assessment literacy levels and their correlation with student outcomes, while thematic analysis of qualitative interviews provided contextual insights. Findings revealed that while educators showed moderate understanding of assessment concepts, significant gaps remain in aligning assessments with learning objectives and adapting them for diverse learners. A positive correlation (R = 0.85, p < 0.001) was found between educators’ assessment literacy scores and student achievement, underscoring the impact of assessment practices on academic performance. Interview data further revealed a need for ongoing training, especially in differentiated and formative assessment techniques. The study concludes that enhancing educators’ assessment literacy is vital to improving student outcomes. It recommends that policymakers, teacher training institutions, and educational leaders implement structured, ongoing professional development programs. Such interventions should focus on building practical assessment competencies that can be adapted across diverse educational settings to drive systemic improvement.